PERBAIKAN DESAIN SISTEM DISTRIBUSI IKAN DENGAN MENGINTEGRASIKAN METODE PHYSICAL DISTRIBUTION SERVICE QUALITY (PDSQ) DAN LEAN SIX SIGMA PADA DISTRIBUSI IKAN DI KABUPATEN SIDOARJO - Wiwik Sulistiyowati (Journal of Engineering and Management in Industrial System, 2015)
Abstract The fresh fish demand increase in the Sidoarjo district can be seen from the fish production amount increase which could be found in the fish market. The fish market became a fresh fish distribution center from fish farmers to customers. To keep the qualities of fish and its distribution services, designing the system design of fish distribution is need to be conducted. The aim of this research is to design a system design of fish distribution by integrating physical distribution service quality (PDSQ ) methods and lean six sigma methods at a fish market in Sidoarjo. This research is conducted to give a suggestion for fisheries and maritime department of Sidoarjo in providing services to public. This research began by measuring the quality of service by using the PDSQ method, then the highest of negative gap value would be identified to find “the waste” by lean method during the distribution process from producer to consumer which affects the quality of service, and than measured capability process using the six sigma method. By using both methods in implementing the system design improvement of fish distribution in Sidoarjo, the results show that the quality of services has increased the distribution of fish by the presence of some improvements facilities. These can be seen from the value of fish qualities which has increased in the reckoning of customer satisfaction from the gap value of each dimensions namely timeline of -2.08  becomes -0.81, availability dimension of -3.36 becomes -1.7, and condition dimension of -1.96 becomes -1.17, and scores of  process capabilities of 4.11 becomes 4.43. The improvement of system design from this existing condition is by involving integrated service unit (UPT) of fish market as a control of the quality of fish and its distribution process to increase the customer satisfaction.